Family History and Risk of Upper Gastrointestinal Cancer in the Linxian General Population - Yang, Huan; Wang, Jian-bing; Zhang, Jin-yu; Fan, Jin-hu; Qiao, You-lin; Taylor, Philip R. (Frontiers in Oncology, 2021)
Abstract Objective The objective of this study was to investigate family history (FH) of upper gastrointestinal (UGI) cancer and risk of esophageal squamous cell carcinoma (ESCC), gastric cardia carcinoma (GCC), and gastric non-cardia carcinoma (GNCC) in the Linxian General Population Nutrition Intervention Trial (NIT) cohort. Methods This prospective analysis was conducted using the Linxian NIT cohort data. Subjects with FH of UGI cancer was treated as an exposed group while the remainders were considered as a comparison group. Hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between FH of UGI cancer and risk of UGI cancer incidence and mortality were estimated using Cox proportional hazards models. Results There were 5,680 newly diagnosed UGI cancer cases during the follow-up period, with a total of 4,573 UGI cancer deaths occurred, including 2,603 ESCC, 1,410 GCC, and 560 GNCC deaths. A positive FH of UGI cancer was associated with a significantly increased risk of ESCC and GCC (Incidence: HRESCC=1.45, 95% CI: 1.35-1.56; HRGCC=1.27, 95% CI: 1.15-1.40; Mortality: HRESCC=1.40, 95% CI: 1.30-1.52; HRGCC=1.27, 95% CI: 1.14-1.42) after adjusting for age at baseline, gender, smoking status, alcohol drinking, education level, and frequency of fresh fruit and vegetable consumption. Subjects with FH in both parents had the highest risk of ESCC and GCC incidence (HR ESCC=1.65, 95% CI: 1.40-1.95; HR GCC=1.42, 95%CI:1.12-1.81) and deaths (HR ESCC=1.65, 95% CI: 1.38-1.97; HR GCC=1.42, 95%CI:1.09-1.85). Spouse diagnosed with UGI cancer did not increase the risk of any UGI cancers of the subjects. In subgroup analysis, FH of UGI cancer was shown to significantly increase the risk of GCC in non-drinkers (Incidence: HR=1.31, 95%CI: 1.17-1.47; Mortality: HR=1.33, 95%CI: 1.17-1.50). No associations were observed for risk of GNCC. Sensitivity analysis by excluding subjects who were followed up less than three years did not materially alter our results. Conclusion Our data point to the role of the FH of UGI cancer to the risk of ESCC and GCC incidence and mortality. The influence of family history on the risk of UGI cancer varies from different types of family members.